AGREED ACTION OF BUSINESS ENTITIES: CONCEPT AND FEATURES - Горбатюк, Яна Вадимівна; Ільєнко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article reveals concepts and features of agreed actions of business entities on the basis of analysis of the norms of the current legislation and scientific views of domestic scientists. Methods: the concept of "agreed actions of business entities" is revealed. The features of agreed actions of business entities are determined. Results: the scientific definition of agreed actions of business entities is proposed. The conclusion is made on the need to improvement the the Law of Ukraine "On the Protection of Economic Competition" in the part of the agreed actions of business entities. Discussion: problems of national legislation and the need to improve it.